Situation Report: Poland, 28 November 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish Delegation for Hungarian Party Congress Polish-German Issue in East-West Relations Kolakowski's Intention to Appeal Reported Poland Expects a Breakthrough in Reducing Grain Imports Polish-Czechoslovak Talks on Economic Cooperation Polish-Bulgarian Trade Protocol Italian Businessmen in Poland Norwegian Foreign Minister to Visit Poland New Polish Ambassador for Canada